How political, spatial, and administrative changes shape the local level: Evidence from municipalities - Luisa Dörr (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2022)
Luisa Dörr prepared this study while she was working at the ifo Center for Public Finance and Political Economy. The study was completed in February 2022 and accepted as doctoral thesis by the Department of Economics at the University of Munich. It consists of three distinct empirical essays investigating various aspects of regional development using data from Germany and Austria. Chapter 2 investigates how far-right populist mayors influence local political culture and economic outcomes. Chapter 3 examines how highway access affects commuting and employment in connected municipalities. Chapter 4 investigates the consequences of municipal mergers on fiscal equalization transfers. The chapters employ regression discontinuity, difference-in-differences, and event study estimations to answer the respective research questions.
Keywords: D72; P16; H72; Z18; H54; O18; H11; H77; R53; 330; Local government; municipalities; populism; far-right politics; partisanpolitics; polarization; immigration; economic policy; budget transparency; highway; infrastructure; accessibility; commuting; employment; municipal mergers; fiscal equalization; expenditures